PHYTOCHEMICAL ANALYSIS OF VITEX ALTISSIMA L. USING UV-VIS, FTIR AND GC-MS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The present study was carried out to characterize the bioactive constituents present in different leaf extracts of Vitex altissima L. using UV-VIS, FTIR and GC-MS. The crude extracts were scanned in the wavelength ranging from 200-1100 nm by using Perkin Elmer Spectrophotometer and the characteristic peaks were detected. For GC-MS analysis, 10 g sample is extracted with 30 ml ethanol, filtered in ash less filter paper with 2 g sodium sulphate and the extract is concentrated to 1 ml by bubbling nitrogen into the solution. The compound detection employed the NIST Ver. 2.0 - Year 2005 library. The biological activities are based on Dr. Duke’s Phytochemical and Ethnobotanical Databases by Dr. Jim Duke of the Agricultural Research Service/USDA. The UV-VIS profile showed different peaks ranging from 400-700 nm with different absorption respectively. The FTIR spectrum confirmed the presence of alcohols, phenols, alkanes, alkynes, alkyl halides, aldehydes, carboxylic acids, aromatics, nitro compounds and amines in different extracts. The results of the GC-MS analysis provide different peaks determining the presence of 21 phytochemical compounds with different therapeutic activities. The major phytoconstituents were n-Hexadecanoic acid (23.74%), 9, 12-Octadecadienoic acid [Z, Z] (23.41%) and Squalene (14.74%). Hence, this study offers a base of using V. altissima as herbal alternative for the synthesis of antimicrobial agents.